AUDIO VISUAL AS ONE OF THE TEACHING RESOURCES ON ILEARNING - Dewi Immaniar Desriant; Untung Rahardja; Reni Mulyani (CCIT Journal, 2012)
Technological developments continue to rise rapidly pushing the educational system to keep pace with technological developments. Education by delivering a good and interesting by utilizing technology as a medium of communication systems to support quality learningquality. But the current system of education and learning is still used conventional and monotonous. Besides the lack of an attractive medium of communication technology make rapid saturation and sometimes student learning materials submitted become fully absorbed. Therefore needed a system and way of teaching a modern and attractive. By using iLearning and utilizing audio visual media as content support can make learning more interesting and certainly more optimally absorbed by the students. This article will discuss the current educational system, identification of problems facing the implementation of iLearning systems that are used as learning, audio visual definition of these, the types of audio visual media that can be applied in learning, a learning system architecture in iLearning. Besides, there are advantages and disadvantages of audio visual media in learning iLearning. In the implementation program listing is displayed by using x-code in iLearning iBooks content. And surveys of student achievement are conveyed through the comparison chart. Audio visual media is a medium that is very helpful in learning, especially in the delivery of educational material with iLearning.Previous learning very monotonous and uninterestingto be a quality learning and optimal absorbed by students.